Implementation of Question and Answer Method in Improving Al-Quran Hadith Learning Outcomes at MTs Negeri 12 Indramayu - Tion Bahrian (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this study was to find out in depth about the application of the question and answer method. This study is a qualitative field study that uses observation methods, direct learning with students, and teacher dialogue at MTs Negeri 12 Indramayu. This study uses a descriptive qualitative approach. Because this study will describe the implementation of the question and answer method. The results of this study indicate that the implementation of the question and answer method in learning the Al-Qur'an Hadith at MTs Negeri 12 Indramayu is quite successful because with the question and answer method students remember what is learned faster and students become more active in following lessons because there is a question and answer process between students and teachers so that the classroom atmosphere becomes lively and for teachers can motivate students to be more active in learning also makes it easier for teachers in implementing learning because the method applied is question and answer not a lecture centered on the teacher but students and teachers are involved.